Penurunan Tingkat Kecacatan di PT Bondi Syad Mulia - Mbau, Ricky Leonardo; Yang Aysia, Debora Anne (Jurnal Titra, 2015)
Abstract: Bondi Syad Mulia is a company which offer the hot dip galvanizing services. Data of disability during the month of April showed that the number of defects that occurred amounted to 12.71%. The aim of this study is to provide a proposal to decrease the number of defects that occur in galvanizing products. There are four (4) types of disability to be studied are bare spots, delamination, welding blowouts, and drainage spikes. Efforts to reduce the level of disability is done by following the steps DMAIC (Define, Measure, Analyze, Improve, and Control). Tools that are used to manage and analyze data is check sheet, pareto chart and fishbone diagrams. Proposed improvements given the company is to make work instructions and records of operators who perform the oven; conduct inspections to check the levels of aluminum in the kettle fluxing by using the inspection form; checking the finished iron or steel in sand blasting and keep records regarding the results obtained in the form of checking; as well as the addition to the initial inspection to check initial thickness and welding conditions on iron or steel.Â Keywords: Quality, DMAIC, Checksheet, Pareto charts, Fishbone diagrams.